2018
DOI: 10.1002/ecs2.2235
|View full text |Cite
|
Sign up to set email alerts
|

Crop rotational diversity increases disease suppressive capacity of soil microbiomes

Abstract: Abstract. Microbiomes can aid in the protection of hosts from infection and disease, but the mechanisms underpinning these functions in complex environmental systems remain unresolved. Soils contain microbiomes that influence plant performance, including their susceptibility to disease. For example, some soil microorganisms produce antimicrobial compounds that suppress the growth of plant pathogens, which can provide benefits for sustainable agricultural management. Evidence shows that crop rotations increase … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
128
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 187 publications
(138 citation statements)
references
References 103 publications
(238 reference statements)
8
128
0
2
Order By: Relevance
“…The bacterial diversity represented by the Shannon Index H' was significantly lower in the higher crop diversity systems (CR7) compared to the lower crop diversity systems (CR1: p = 0.0478; CR3: p = 0.0263; CR5: p = 0.0208). Similar to the studies of Soman et al [38] and Peralta et al [39], the differences in the structure of communities were not widely reflected in Shannon Index H', indicating the necessity of using more indicators in order to understand differences between bacterial communities. The true richness and diversity, measured in estimated number of T-RFs, rather than Shannon Index H', might better highlight the hypothetical influence of crop rotations on bacterial communities.…”
Section: Richness and Diversity Of Bacterial Communitiessupporting
confidence: 78%
See 1 more Smart Citation
“…The bacterial diversity represented by the Shannon Index H' was significantly lower in the higher crop diversity systems (CR7) compared to the lower crop diversity systems (CR1: p = 0.0478; CR3: p = 0.0263; CR5: p = 0.0208). Similar to the studies of Soman et al [38] and Peralta et al [39], the differences in the structure of communities were not widely reflected in Shannon Index H', indicating the necessity of using more indicators in order to understand differences between bacterial communities. The true richness and diversity, measured in estimated number of T-RFs, rather than Shannon Index H', might better highlight the hypothetical influence of crop rotations on bacterial communities.…”
Section: Richness and Diversity Of Bacterial Communitiessupporting
confidence: 78%
“…The true richness and diversity, measured in estimated number of T-RFs, rather than Shannon Index H', might better highlight the hypothetical influence of crop rotations on bacterial communities. Rotation has been widely considered as one of the most promising practices for the improvement of soil microbial diversity [39][40][41]. However, according to our results, the lowest diversity was found in the bacterial community associated to the most intense rotation system studied (Norfolk-type).…”
Section: Richness and Diversity Of Bacterial Communitiesmentioning
confidence: 45%
“…Recent studies have shown that the genetic background of the test plant can determine the root-associated microbiome and whether conspecific plant-soil feedback effects on plant growth are negative or neutral (Hu et al, 2018;Carrillo et al, 2019). This has been an oft-overlooked aspect during the breeding process (P erez-Jaramillo et al, 2016;Carrillo et al, 2019), and here we show that a certain crop or cultivar may inhibit beneficial microbial groups such as mycorrhiza.…”
Section: Researchsupporting
confidence: 52%
“…The soil is the source of most beneficial microbes that colonize the rhizosphere (Bulgarelli et al, 2013) the thin interface of root surface with attached soilwhich are key players in plant immunity and overall plant performance. To date, soil management typically focuses on avoiding detrimental effects such as allelopathy or accumulation of pathogens and pests via crop rotation (Peralta et al, 2018). However, an exciting possibility is to manage soils to steer microbial communities to a desired beneficial state with a focus on promoting the presence and activity of beneficial microbes, instead of simply avoiding the pathogenic ones.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, the rhizosphere supports a marked proliferation and enrichment of specific microorganisms (Jones et al 2009). Beneficial microorganisms associated with plant roots can play an important role in nutrient uptake and plant growth (Gaiero et al 2013), disease suppression (Peralta et al 2018), reducing damage from pests (Elhady et al 2018), and resilience during periods of stress (Gaudin et al 2015). The advent of molecular techniques has facilitated a more comprehensive investigation of biodiversity and function at the root surface.…”
Section: Crop Rotationmentioning
confidence: 99%